When the sky breaks : hurricanes, tornadoes, and the worst weather in the world - Winchester, Simon (Viking, an imprint of Penguin Random House LLC, 2017)
A look at storms, covering tornadoes, hurricanes, and other severe weather and discussing when, where, and how they form.